2011
DOI: 10.1111/j.1467-9450.2011.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Target‐mask shape congruence impacts the type of metacontrast masking

Abstract: Visual metacontrast masking may depend on the time intervals between target and mask in two qualitatively different ways: in type-A masking the smaller the mask delay from target the stronger the masking while in type-B masking maximal masking effect is obtained with a larger temporal delay of the mask. Variability in the qualitative apperance of masking functions has been explained by variability in stimuli parameters and tasks. Recent research on metacontrast masking has surprisingly shown that both of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 33 publications
8
25
0
Order By: Relevance
“…These results collectively support our earlier findings and rule out eye movement as an explanation for elimination of masking effect under predictable group motion condition. As mentioned, there have been reports of individual differences in masking functions; for example, for the same stimulus parameters, some subjects exhibit Type-A, whereas others have Type-B masking functions (Albrecht et al, 2010;Maksimov et al, 2011). Whereas much of this difference can be explained by different criterion contents used by subjects, there remains a possibility of inherent differences between subjects.…”
Section: Masking By Structure With Predictable Ternus-pikler Directionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results collectively support our earlier findings and rule out eye movement as an explanation for elimination of masking effect under predictable group motion condition. As mentioned, there have been reports of individual differences in masking functions; for example, for the same stimulus parameters, some subjects exhibit Type-A, whereas others have Type-B masking functions (Albrecht et al, 2010;Maksimov et al, 2011). Whereas much of this difference can be explained by different criterion contents used by subjects, there remains a possibility of inherent differences between subjects.…”
Section: Masking By Structure With Predictable Ternus-pikler Directionmentioning
confidence: 92%
“…In other words, the metacontrast masking function appears to shift from type-B to type-A. The expression of type-A versus type-B metacontrast functions has been attributed to differences in stimulus parameters, criterion contents, or individual differences (Breitmeyer & Öğmen, 2006;Duangudom, Francis, & Herzog, 2007;Francis & Cho, 2008;Albrecht, Klapotke, & Matler, 2010;Maksimov, Murd, & Bachmann, 2011). In our study, the same subjects were used in the two conditions and the inspection of individual subject data showed that all subjects' metacontrast functions consistently showed increased masking at short SOAs in the Ternus-Pikler condition compared to the static control condition.…”
Section: Methodsmentioning
confidence: 99%
“…In one of our earlier papers using this paradigm we showed that there is indeed interaction between genetic variability exemplified in BDNF Val66Met, NRG1/rs6994992, and 5-HTTLPR polymorphisms on the one hand and certain behavioral effects of metacontrast on the other hand [18]. In the present study we used metacontrast data from that earlier experiment where stimuli and procedure were the same as in [14][15][16] and carried out new genotyping for 5HTR2A-1438A/G (rs6311).…”
Section: Introductionmentioning
confidence: 95%
“…Metacontrast masking functions can be either monotonically increasing (type-A functions) or nonmonotonic (type-B functions) [10,11]. Both the qualitative and quantitative expression of masking often depends also on the congruency between the target and mask shapes [14][15][16][17]. For example, in the trials with congruent target/mask shape when the target is square-shaped then mask is also square-shaped, but an incongruent mask for the square-shaped target represents a diamond shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation